The Relationship Of Islamic Business Ethics With Muamalah Fiqh And Islamic Alliance Law - Humaira Siti Salma, Shofya; Anwar, Syahrul; Kania, Dede (Zona Law And Public Administration Indonesia, 2024)
This article discusses the relationship between Islamic business ethics, fiqh muamalah, and Islamic law of engagement in the context of Islamic business. Islamic business ethics is an important aspect of Islamic business principles, which emphasize the importance of ethical behavior in business transactions. Fiqh muamalah, as part of Islamic law, provides the legal framework that governs business transactions and other economic activities in Islam. Islamic law of obligations also plays a crucial role in regulating contracts and agreements in business. The researcher used a qualitative methodology. The data was obtained from books, relevant journals and the internet. The method of analysis used is descriptive analysis. The results of this study show that there is a close relationship between Islamic business ethics, fiqh muamalah and Islamic binding law. This is because fiqh muamalah is a branch of fiqh science that deals with the rules and laws that apply to transactions, business, and engagement in daily life, including in the business context. By adhering to Islamic business ethics, understanding fiqh muamalah, and following Islamic laws, Muslim business people can help create a more ethical business environment that is in line with Islamic values.